The Influence of The Use of Learning Media on The Material on The Properties of Light on The Learning Outcomes - Sari, Meirita; Yunilarosi, Elvida Sari; Apriani, Intan; Hardila, Lionita Dewi; Pratama, Sigit Surya (Program Studi Tadris IPA, Fakultas Tarbiyah dan Ilmu Keguruan, Universitas Islam Negeri (UIN) Syekh Wasil Kediri, 2026)
This study examined the effect of using learning media in teaching the properties of light on junior high school students’ learning outcomes and critical thinking skills in science. A quantitative approach was employed using a one-group pre-test–post-test design. The sample was selected randomly, and data were collected through a critical thinking test administered before and after the treatment. The findings revealed that the use of learning media had a positive and significant impact on students’ performance. Students’ mean score increased from 54.81 on the pre-test to 82.90 on the post-test, indicating substantial improvement in learning outcomes. In addition, students’ critical thinking skills showed marked development, improving from a low category to an excellent level after the implementation of the learning media. Statistical analysis using the t-test further confirmed that the treatment significantly enhanced students’ critical thinking abilities. These results suggest that integrating learning media into science instruction, particularly in the topic of the properties of light, effectively supports students’ understanding and promotes higher-order thinking. Overall, the study concludes that the use of learning media not only improves academic achievement but also fosters critical thinking skills, which are essential for students’ success in science learning.